Dłonie i motywy związane z rękami w kreatywnej reklamie wizualnej - Pawłowska-Jądrzyk, Brygida (Załącznik Kulturoznawczy, 2023)
Hands and Hand-Related Motifs in Creative Visual Advertising The author summarizes typical ways of using the motif of hands in advertising, then focuses on examples of creative advertising, i.e. a form of marketing that, as a rule, aims to attract attention by breaking the presentation schemes, surprising, and often also shocking the recipient. The following types of advertisements can be distinguished within this category: (1) advertisements based on transsemiotic delexicalization of phrases or expressions related to hands or activities performed with them; (2) advertisements ascribing to hands some extraordinary features or properties that conflict with common knowledge about the world and as such require a non-literal interpretation; (3) advertisements relying on the animalization or reification of hands; (4) advertisements featuring hand/palm/finger themes in unusual, drastic, or obscene situational contexts; (5) advertisements in which motifs related to hands are an element of intertextual play of meanings.